Kesesuaian Lahan untuk Pengelolaan Hutan oleh Rakyat Guna Pengentasan Kemiskinan di Kawasan Perbatasan Kabupaten Timor Tengah Utara - Fransiscus Xaferius Herwirawan (Graduate School Bogor Agricultural University (SPs IPB), 2019)
AbstractThis study analysed the suitability of land use for community forestry in the semi-arid region on the island of West Timor, exactly on the border between Indonesia and East Timor. The purpose of this study is to determine the most suitable location for community forest management based on the specified parameters. The analytical method used is the Multi Criteria Evaluation (MCE). The MCE employing five parameters and determine the criteria for each of the parameters through preliminary surveys, namely: rainfall, land slope, soil type, distance to local roads, and the distance from the state border. Weight for each parameter is determined using process hierarchy analysis (PHA) with expert opinion, then integrated the results from PHA into GIS to determine the location of lands eligible for community forest management. The results of analysis showed there is an area of 4,943 ha (6.7%) eligible to be managed by the community in the border region in North Central Timor. The lands spread across 43 villages and are in various size. Small-scale, simple and economical forest management can be introduced in these 43 villages. It is projected that this initiative can have significant poverty alleviation effect. The initiative can enable people in 11 villages (27%) to move out of national poverty standard and people in 4 villages (12%) to move out of international 2PPP poverty standard.